Enhancing Students’ Speaking Ability by Using Story Telling Technique (STT) - Andrian Andrian; Faudi Faudi (Budapest International Research and Critics University, 2020)
Enhancing Students’ Speaking By Using Story Telling Technique (STT) (An Experimental Research at MTsN 2 Aceh Besar). This research aimed to find out the students’ speaking ability by using story telling technique, the focus is on fluency and vocabulary in speaking. The instruments of the researcher is test and questionnaires. The main subjects of this researcher are 32 students of VIII-I at MTsN 2 Aceh Besar. The data quantitative and qualitative. The quantitative data is gained from test and the qualitative data is gained from questionnaires. After analyzing data, the score of pre-test the lowest score is 20 and the higher score is 50. After applying the technique she give the students post-test score could be seen in the table 4.1.6 (60 and 85). While the lowest value of questionnaires is 0% and the highest value is 68.75%. Based on the score, it is suggested that the teacher should help and understand their students before teaching them. This can be done by giving the students’ chose to ask questions, involve in discussing, express their ability in English, and try to help the students to investigate and solve their problems in learning English. Moreover, the students should increase their ability in English by trying to enrich their knowledge and reading related books.